2012
DOI: 10.1002/elps.201100505
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis: A model to transport drugs directly into teeth

Abstract: The article describes an innovative delivery system based on the principles of dielectrophoresis to transport drugs directly into site-specific intraoral targets. The hypothesis that a drug can be driven into tooth enamel during the application of an applied electrical potential difference was tested by the authors in in vitro studies comparing dielectrophoresis to diffusion to transport carbamide peroxide and fluoride. The studies showed that these agents can be transported directly into teeth using an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…When this technology becomes clinically feasible, it may reduce the oral systemic route of many drugs, overcoming the disadvantages of peroral route administration, and allowing fast delivery of drugs to the pulp tissue. 41 With regard to the bleaching outcome, the results of this study indicated that both groups demonstrated equivalent and significant tooth shade enhancement when compared with the baseline (Table 3), and thus the third null hypothesis was not rejected. The comparison of shade change after in-office bleaching with existing literature is difficult, due to the different methods of measurement (shade guides and spectrophotometers) and different units of measurement (eg, CIELab system, shade guide units) employed.…”
Section: Discussionmentioning
confidence: 76%
“…When this technology becomes clinically feasible, it may reduce the oral systemic route of many drugs, overcoming the disadvantages of peroral route administration, and allowing fast delivery of drugs to the pulp tissue. 41 With regard to the bleaching outcome, the results of this study indicated that both groups demonstrated equivalent and significant tooth shade enhancement when compared with the baseline (Table 3), and thus the third null hypothesis was not rejected. The comparison of shade change after in-office bleaching with existing literature is difficult, due to the different methods of measurement (shade guides and spectrophotometers) and different units of measurement (eg, CIELab system, shade guide units) employed.…”
Section: Discussionmentioning
confidence: 76%
“…The ability to manipulate biological particles (cells, viruses, proteins, DNA molecules) is important for biomedicine , biotechnology , and other fields related to biological micro‐ and nanoobjects.…”
Section: Introductionmentioning
confidence: 99%
“…The precise control of particles, especially cells, viruses, proteins, DNA molecules and other biological particles, has widespread application prospects in biomedical [6], bioscience [7] and other fields [8]. …”
Section: Introductionmentioning
confidence: 99%